The Nonsurgical Management of Orbital Dystopia Using Refractive Lenses and Prosthetic Shells. Issue 6 (September 2018) - Joganathan, Varajini; Terry, Patsy; Wall, Steve; Norris, Jonathan H.
Abstract : Abstract: Surgical rehabilitation of orbital dystopia can be challenging. The authors demonstrate the effective use of spectacle lenses to visually correct misalignments of the globe and the orbit. Presented is a retrospective review of 4 patients undergoing aesthetic rehabilitation through use of spectacle lenses and in a number patients a cosmetic shell. Two patients with neurofibromatosis presented with inferior dystopia of the globe and orbit. A base-down prismatic lens applied to the spectacles in conjunction with a prosthetic shell successfully visually corrected the facial asymmetry and improved patients' aesthetic appearance. One patient with a history of traumatic retinal detachment, who did not want any surgical intervention, a "plus" (hypermetropic) lens was used to magnify the perceived image of an enophthalmic and phthisical globe, to enhance appearance and improve symmetry. In the fourth patient, with Goldenhar syndrome, the appearance of a hypotropia and concurrent esotropia was successfully treated with a Fresnel prism and a prosthetic shell. This case series illustrates the successful role of various refractive lenses often in conjunction with prosthetic shells in patients with reduced vision and orbital dystopia to improve facial symmetry. This conservative treatment is especially useful when surgery is not a desired or not considered a suitable option for the patient.